Remote sensing techniques as a tool for detecting water outflows. The case study of Cephalonia Island. p.1519 - Stefouli, M.; Vasileiou, E.; Charou, E.; Stathopoulos, N.; Perrakis, A.; Giampouras, P. (Bulletin of the Geological Society of Greece, 2013)
The amount of water flowing into the seas and oceans has slowly but steadily increased in recent years, signifying a possible speeding up of the water cycle due to climate change. The detection of the water outflows and the exploitation of them are very important to the rational water management. Remote sensing techniques has been proven a valuable tool for the detection and identification of submarine groundwater discharge-SGD (Submarine Groundwater Discharge). In this study the island of Cephalonia in Ionian sea, Greece is considered as a case study. A 6 Km sea buffer zone around the island is studied using Landsat images. Submarine groundwater discharge has been detected through remote sensing methods and the results have been combined with the tectonism and hydrogeological conditions of the island. A quantitative analysis of temperature in the buffer zone was carried out. The sea thermal anomalies in the same zone were also investigated.